Italian Children's Accounts of the Lockdown: Insights and Perspectives. - Capurso, Michele; Pedale, Tiziana; Santangelo, Valerio; Salmi, Luciana Pagano; Mazzeschi, Claudia (Journal of Child & Family Studies, 2023)
COVID-19 lockdown-imposed restrictions emerged as a risk to children's well-being. However, the extant literature often ignored children's experiences, emotions, struggles, hopes, and expectations. Based on a large sample of Italian students (N = 906; mean age = 9.4 years, 48.8% female), we drew data from a post-lockdown school re-entry program where students completed narrative activities in 2020. These narratives underwent quantitative content analysis according to gender and school level. Overall, children reported mixed feelings about the lockdown; they felt safe at home but also experienced fear and missed their friends, school, and freedom. Screen-time, technology and friendships helped, but children struggled to make sense of the events. Our findings show how children attempted to make sense of the lockdown experience and may provide key information for the development of community coping programs to help children facing crises in the future. Highlights: Children narrated their lockdown experiences as part of a post lockdown school re-entry program. We identified, coded, classified, and evaluated their narratives to examine perception and coping mechanisms utilized during the covid pandemic. Family, friendship, and relationships helped children to deal with the impacts of the pandemic and with the forced isolation. Children suffered from the loss of physical contacts with peers, freedom, and school. Understanding children's experience during a crisis can benefit the future development of crisis coping programs.